How to Deal with Pulpitis: An Overview of New Approaches - Jakub Fiegler-Rudol; Wojciech Niemczyk; Katarzyna Janik; Anna Zawilska; Małgorzata Kępa; Marta Tanasiewicz (Dentistry Journal)
Background: Traditional root canal therapy (RCT) effectively removes diseased or necrotic pulp tissue and replaces it with inorganic materials. Regenerative endodontics is an alternative to conventional RCT by using biologically based approaches to restore the pulp–dentin complex. This review explores emerging techniques, including autogenic and allogenic pulp transplantation, platelet-rich fibrin, human amniotic membrane scaffolds, specialized pro-resolving mediators, nanofibrous and bioceramic scaffolds, injectable hydrogels, dentin matrix proteins, and cell-homing strategies. These methods utilize stem cells, growth factors, and biomaterials to regenerate vascularized, functional pulp tissue. Methods: A narrative review was conducted using PubMed, Scopus, and Embase to identify studies published between 2010 and 2023. In vitro, animal, and clinical studies focusing on innovative regenerative endodontic techniques were analyzed. Conclusions: Although regenerative endodontics demonstrates great potential, challenges remain in standardizing protocols, addressing biological variability, and achieving consistent clinical outcomes. Future research must focus on refining these techniques to ensure their safety, efficacy, and accessibility in routine practice. By addressing current limitations, regenerative endodontics could redefine the management of pulpitis, offering biologically based treatments that enhance tooth vitality, structural integrity, and long-term prognosis.